Loss of astrocyte cholesterol synthesis disrupts neuronal function and alters whole-body metabolism - Ferris, Heather A. (Proc Natl Acad Sci U S A, 2017)
Cholesterol is important for normal brain function. The brain synthesizes its own cholesterol, presumably in astrocytes. We have previously shown that diabetes results in decreased brain cholesterol synthesis by a reduction in sterol regulatory element-binding protein 2 (SREBP2)-regulated transcription. Here we show that coculture of control astrocytes with neurons enhances neurite outgrowth, and this is reduced with SREBP2 knockdown astrocytes. In vivo, mice with knockout of SREBP2 in astrocytes have impaired brain development and behavioral and motor defects. These mice also have altered energy balance, altered body composition, and a shift in metabolism toward carbohydrate oxidation driven by increased glucose oxidation by the brain. Thus, SREBP2-mediated cholesterol synthesis in astrocytes plays an important role in brain and neuronal development and function, and altered brain cholesterol synthesis may contribute to the interaction between metabolic diseases, such as diabetes and altered brain function.